Exploration of deep eutectic solvent-based biphasic system for furfural production and enhancing enzymatic hydrolysis: Chemical, topochemical, and morphological changes. (May 2022) - Sun, Li-Li; Yue, Zhuang; Sun, Shao-Chao; Sun, Shao-Ni; Cao, Xue-Fei; Yuan, Tong-Qi; Wen, Jia-Long
Graphical abstract: Highlights: An efficient DES/2-MTHF biphasic system was exploited to deconstruct Eucalyptus . A maximum furfural yield of 54.7% and enzymatic efficiency of 97.0% was achieved. 100% hemicelluloses and 92.0% lignin were removed under optimized conditions. Chemical and anatomical features synergistically affected the enzymatic hydrolysis. Abstract: Developing a biorefinery process for a highly integrated valorization and fractionation of lignocellulose is crucial for its utilization. Herein, a biphasic system comprising choline chloride/lactic acid and 2-methyltetrahydrofuran with Al2 (SO4 )3 and H2 SO4 as catalysts was applied to pretreat Eucalyptus . Results showed that under the optimized conditions (150 °C, 30 min, 0.2 M Al2 (SO4 )3, 0.075 M H2 SO4 ), the furfural yield and enzymatic hydrolysis efficiency could reach 54.7% and 97.0%, respectively. The efficient cellulose conversion was attributed to remarkable removal of lignin (91.0%) and hemicelluloses (100.0%), thereby causing the disruption of cell wall structure and enhancement of cellulose accessibility. Meanwhile, confocal Raman microscope and atomic force microscope displayed that the pretreatment resulted in the decreasing intensities of carbohydrates and lignin different regions of cell walls, and exposing of the embedded microfibers from noncellulosic polymers. Overall, the deep eutectic solvent-based biphasic system displayed high performance for effective utilization of carbohydrate components in lignocellulose.